The Impact of Online Competition on Local Newspapers: Evidence from the Introduction of Craigslist - Milena Djourelova; Ruben Durante; Gregory J. Martin (Center for Economic Studies and Ifo Institute (CESifo), 2021)
How does competition from online platforms affect the organization, performance, and editorial choices of newspapers? And what are the implications of these changes for the information vot-ers are exposed to and for political accountability? We study these questions using the staggered introduction of Craigslist - the world's largest online platform for classified advertising - across US counties between 1995 and 2009. This setting allows us to separate the effect of competition for classified advertising from other changes brought about by the Internet, and to compare newspapers that relied more or less heavily on classified ads ex ante. We find that, following the entry of Craigslist, local papers experienced a significant decline in the number of newsroom and management staff. Cuts in editorial staff disproportionately affected reporters covering politics. These organizational changes led to a reduction in news coverage of politics and political corrup-tion, and resulted in a decline in newspaper readership which was not compensated by increased news consumption on other media. Finally, we find some evidence that reduced news coverage of politics was associated with lower voter turnout, and more party-line voting for both citizens and politicians.
Keywords: L82; L86; D72; 330; newspapers; internet; advertising; political accountability